2012
DOI: 10.1063/1.4707417
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional high Seebeck coefficient and gas-flow-induced voltage in multilayer graphene

Abstract: Monolayer graphene shows Seebeck coefficient several times and gas-flow-induced voltage twenty times higher than that of bulk graphite. Here we find that the Seebeck coefficient of multilayer graphene increases monotonically with increasing layer and reaches its peak value at hexa-layer ~77% higher than for monolayer and then decreases, although the electric resistance decreases monotonically with increasing layer. The flow-induced voltage is significantly higher in 2, 4, 5, 6, 7 layered graphene than in 1, 3,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 32 publications
(45 reference statements)
4
33
3
Order By: Relevance
“…Different from the monolayer–bilayer junction, the peak S is larger in monolayer graphene than in multilayer graphene. It has been experimentally demonstrated that S varies nonmonotonically with the number of graphene layers; it increases first from monolayer to hexa‐layer with a maximum value (54 µV K −1 ) and then gradually decreases to that of graphite flake (13 µV K −1 ) . Our peak S of multilayer graphene is close to this bulk value.…”
Section: Resultssupporting
confidence: 69%
“…Different from the monolayer–bilayer junction, the peak S is larger in monolayer graphene than in multilayer graphene. It has been experimentally demonstrated that S varies nonmonotonically with the number of graphene layers; it increases first from monolayer to hexa‐layer with a maximum value (54 µV K −1 ) and then gradually decreases to that of graphite flake (13 µV K −1 ) . Our peak S of multilayer graphene is close to this bulk value.…”
Section: Resultssupporting
confidence: 69%
“…5 for the 100 and 200 Hz datasets. Here, a consistent linear dependence is observed between the voltage and the temperature gradient, yielding Seebeck coefficients of -97.1 μV/K and -99.3 μV/K for the 100 and 200 Hz datasets, respectively, which are higher than the in- plane Seebeck coefficients of single layer graphene, ~50 μW/K, at room temperature [29]. The Seebeck coefficient is negative in these devices, since the band offsets (and hence energy barriers) between graphene and BN are much smaller for electrons than holes.…”
supporting
confidence: 62%
“…Regarding graphene, multiple active Nano Res. studies have explored their properties for energy production [18,19]. Recently, graphene was reported to generate an induced voltage by moving a droplet of ionic liquid along the material [20].…”
Section: Introductionmentioning
confidence: 99%